HLA-B*58:01 screening in Asia-Pacific is an ethical imperative – not just a cost question - Ng, Wei Leik; Tse, Emily Tsui Yee; Oka, Prawira; Lim, Hooi Min; Koh, Sky Wei Chee; Ramli, Rizawati; Lau, Hung Chiun; Lam, Benjamin Chih Chiang; Goldsmith, Laurie J.; Abdullah, Adina; Goh, Lay Hoon (University of Edinburgh, 2025)
Allopurinol remains the first-line treatment for gout; however, it carries a risk of severe cutaneous adverse reactions (SCARs), particularly among carriers of the HLA-B*58:01 allele. In the Asia-Pacific region, screening practices vary widely due to infrastructure gaps, cost concerns, and differing health policies. For example, while cost-effectiveness analyses have influenced screening decisions in some countries, they often overlook long-term health system burdens and ethical imperatives. Therefore, screenings should not be withheld solely on economic grounds, especially when they can prevent life-threatening outcomes. For that reason, a targeted, risk-based approach that integrates genetic and clinical factors could offer a practical and equitable path forward, improving pharmacogenomic literacy, expanding access to testing, developing regional data-sharing platforms, and involving patients in co-designing screening strategies. Rapid point-of-care testing and integration of screening process with existing care pathway may further support this implementation. However, a coordinated regional effort is needed to ensure safer prescribing and equitable access to pharmacogenomic screening across diverse healthcare settings.